Using recycled plastic waste as fiber reinforcement on limestone residue mortar - Bendjillali, Khadra; Chemrouk, Mohamed (Revista de la Construcción. Journal of Construction, 2024)
The main purpose of the paper is to study the effect of the geometry of recycled plastic fiber on the performance of mortar basing on natural limestone residue. The used fibers were collected from plastic waste of polypropylene, resulting from domestic sweeps fabrication. Two types of recycled fibers were used, straight and crimped fibers, which have the same length (20 ± 2 mm) and the same diameter (0.45 ± 0.07 mm). Four dosages of fibers were considered, 0.5, 1, 1.5 and 2 wt. %. The obtained results show that the geometry of recycled plastic fibers has an important effect on the performances of limestone residue mortar. The addition of recycled fibers to mortar decreases its workability and the decrease is higher with crimped fibers. The results revealed that the limit dosage of recycled plastic fiber necessary to obtain a workable mortar is 1 % and 0.5 % for straight and crimped fibers, respectively. The benefit of recycled plastic fibers is well observed on the flexural and compressive behavior of limestone residue mortar, but the strength’s values are higher in straight fibers mortar (SFM) than that in crimped fibers mortar (CFM). The microstructure analysis confirms the good performances of the fiber mortar.